Coming Home: A Screenplay Exploring Effects of Parental Divorce to Adult Children’s Perception of Romantic Relationship - Feren Faith Chesia; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This thesis and the screenplay written based on the research aims to illustrate how a parents’ act of divorce can severely impact their offspring’s perception of romantic relationships despite having reached the age of adulthood. In this creative work, Tania, the main protagonist, had to witness her parents who seemed perfectly happy together divorce when she was 19. Referring to the theory of relational trauma by Samantha L. Anders, this moment causes a deep trauma for Tania which becomes suppressed and unresolved during later parts of her life. The story emphasizes Tania's struggle towards healing; with healing being a decisional step centered on Tania herself. Thus, the creative work will place the major spotlight on Tania and how she finally has to confront aspects of her unresolved trauma when suddenly receiving a marriage proposal from her boyfriend.